Development of Animated Videos as A Medium for Learning Mandarin - Fatmawati, Fatmawati; Hukmawati, Hukmawati; Marsuki, Ria Riski; Pasang, Kezia Yansen (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2024)
This study aims to examine the use of animated videos as a medium for learning Chinese, focusing on the main challenges faced by learners, such as mastering the tonal system and Hanzi characters. The literature review was conducted by collecting and analyzing various relevant sources to evaluate the effectiveness of animated videos in improving Chinese comprehension. This research found that animated videos have great potential in facilitating complex language learning. Through clear and interactive visualizations, animated videos can help learners understand the different tones in Chinese, as well as make it easier for them to remember and write Hanzi characters. In addition, they also offer learning flexibility, allowing learners to access materials anytime and anywhere, supporting the concept of self-directed learning. This research also highlights the importance of cultural integration in animated videos, which not only teach the language, but also introduce Chinese cultural contexts related to language use. By analyzing various research studies and reports, this research provides recommendations for the development of more innovative animated videos that meet the needs of Chinese language learning. The results of this study can contribute to the development of more effective and fun learning media for Mandarin learners, especially at the beginner level.